Economics of orthodox tea production: a case of Ilam, Nepal - Tiwari, A.; Adhikari, K.B.; Dhungana, S.M. (Journal of Agriculture and Environment, 2018)
Research on economic analysis of conventional orthodox tea in Ilam district of Nepal was conducted by selecting Fikkal and Kanyam area of Suryodaya Municipality purposely. The average area under tea cultivation was 0.67 hectares per household in Fikkal area and 0.57 hectares per household in Kanyam area. The average productivity of green leaf in Fikkal area was found slightly higher than Kanyam area. The average cost of green leaf production per ropani in Fikkal area was found higher than Kanyam area. It was more in small category compared to large category in both study area. This signified the principle of economies of scale. Gross margin per hectares was positively correlated with increased farm size in both the study areas. Overall benefit-cost ratio was greater than one in both the study areas. The study revealed the scarcity of quality inputs and inadequate technical knowhow, quick perishability of green leaf, price instability, and unavailability of auction market, weak horizontal coordination and vertical coordination at the different stages of tea value chains were the major problems in the study area.